The wild card selected poems, early and late - Shapiro, Karl (Univ. of Illinois Press, 1998)
As Shapiro's subjects have evolved, so has his style, developing and modulating into various forms, but always with an essential rhythm and lyricism. To read Shapiro's work as it unfolds in The Wild Card will be to grasp the depth and breadth of a great poet's career and the many sides of his nature
Keywords: Poetry